THE PROBLEM OF PROFESSIONAL AND MODERN LEXICOLOGY - Abdullaeva Dilfuza Babakhanovna (Journals Park Publishing, 2024)
This article examines the concept of professionalism in modern lexicography. It explores the challenges and complexities lexicographers face in maintaining high standards of professionalism while adapting to the evolving needs of language users in the digital age. The problems facing these professionals today are multifaceted and complex. They should not only keep up with the rapid introduction of new terms and applications influenced by technology and cultural shifts, but also meet the increasing demand for dictionaries to be both comprehensive and usable on various digital platforms.
Keywords: professionalism, modern lexicography, language evolution, digital age, lexicon, language users, standards, problems, complexities.